The reliability of physiological and performance data obtained during a long distance simulated triathlon laboratory test - Luckin, K. M. (Journal of Science and Cycling, 2019)
The aim of this study was to investigate the reliability of a newly developed long distance (LD) simulated triathlon for testing performance and physiological changes in LD triathletes. Ten trained LD triathletes (mean ± standard deviation: age 34.1 ± 5.0 years, body mass 69.07 ± 13.89 kg) completed two separate trials of a simulated LD triathlon consisting of a 1500 m swim, a 60 minute cycle at 60% of power at VO2max and a 20 minute run at 70% of velocity at VO2max. Performance (time, pace, power and rating of perceived exertion) and physiological (economy of movement (oxygen cost and energy consumption), blood lactate and heart rate)variables were measured throughout the simulated LD triathlon. Coefficient of variations (CV %) and intra class correlation coefficients (ICC) were calculated to determine reliability. The current study displayed a high level of reliability, with moderate to excellent ICC measurements for performance and physiological variables (ICC 0.62-0.99). All physiological variables, except blood lactate, demonstrated CV values < 10%. In conclusion, the newly developed LD simulated triathlon has a high level of task representation for LD triathletes and can accurately assess performance changes in a research setting.